Physical properties of new binary antiferroelectric liquid crystal mixtures. (1st February 2018) - Fitas, Jakub; Jaworska-Gołąb, Teresa; Deptuch, Aleksandra; Tykarska, Marzena; Kurp, Katarzyna; Żurowska, Magdalena; Marzec, Monika
ABSTRACT: Three newly prepared binary mixtures exhibiting chiral tilted smectic phases have been studied using differential scanning calorimetry, dielectric spectroscopy and electro-optic method, as well as X-ray diffraction. Broad temperature range of ferroelectric and antiferroelectric phases was detected in these mixtures and temperature dependence of spontaneous polarization, tilt angle and switching time were measured for all of them. It's occurred that all of the studied mixtures are orthoconic antiferroelectric liquid crystals. Based on the X-ray diffraction results, the temperature dependence of layer thickness in the paraelectric, ferroelectric and antiferroelectric phases was found. By using dielectric spectroscopy, Goldstone mode was identified in the ferroelectric phase, while antiphase fluctuations of azimuthal angle have been found in the antiferroelectric phase. Based on the results of the complementary methods, the transition temperatures were found as well as the order of the para-ferroelectric phase transition was determined as non-continuous one with critical parameter β equal to ca. 0.25.